Impact of Gender on Labor Force Participation - Markita Joi Alunan; Andrea Sofia Aquino; Frances Nicole Loto; Marie Antoinette Rosete (Faculty of Science and Technology University of Pramita Indonesia, 2023)
Previous studies have revealed that marital status and gender roles affect the totality of labor force. Societal norms that have been existing from hundreds of years ago are still prevalent nowadays. Unequal treatments are still present and mostly the disadvantage are females. This research tackles whether gender (male and female) would have an effect or has a relationship with the number of hours worked by people in Luzon, Visayas, and Mindanao. It further discusses the reason behind whether it affects or doesn’t affect the number of hours worked. Data from Philippine Statistics Authority from 1991 to 2020 is used as a basis and reference data to test whether gender affects the number of hours worked in those regions. Luzon, Visayas, and Mindanao is used due to the reason that it is Philippine’s three major islands which is composed of several provinces and regions. Ordinary Least Squares is used to test whether there is a significant relationship between said variables and upon testing, in which resulted that there is no significant relationship.